Insight into the formation, structure and digestibility of lotus seed amylose-fatty acid complexes prepared by high hydrostatic pressure. (June 2019) - Guo, Zebin; Jia, Xiangze; Lin, Xiong; Chen, Bingyan; Sun, Siwei; Zheng, Baodong
Abstract: Lotus seed amylose-fatty acid complexes were prepared using high hydrostatic pressure and the relationship between their structural properties and digestibility was investigated. The formation of lotus seed amylose-fatty acid complexes increased the values of weight molar mass ( Mw ), number molar mass ( Mn ), polydispersity index and resistant starch content compared to those of amylose controls. Mw and Mn values of lotus seed amylose and complexes decreased with an increase in high hydrostatic pressure from 500 MPa to 600 MPa, suggesting that the lotus seed amylose was decomposed into short glucan chains. The presence of single helical lotus seed amylose-fatty acid complexes and double helical retrograded amylose was investigated using Raman spectroscopy and imaging. The results from Raman spectra and in vitro digestion showed that the content of both single helical LSA-fatty acid complexes and double helical retrograded LSA were responsible for digestibility of the complex matrix.